Litigating the environment : process and procedure before international courts and tribunals - Bendel, Justine (United Kingdom: Edwars Elgar Publishing Limited, 2023)
Providing an insightful contribution to literature on the topic, this book scrutinizes how international courts and tribunals may respond procedurally to an ever-growing list of environmental disputes. In a time of environmental crisis, it lays crucial groundwork for strengthening the application of international environmental law, a topic of increasing relevance for global civil society. Putting into perspective the practices of various international courts and tribunals, the author works within the constraints of the existing judicial framework to sharpen international environmental justice and governance. Bendel provides judges and litigators with tools that they can use when confronted with environmental disputes, to extract the best practices in the interest of improving environmental litigation for each phase of a judicial procedure. This state-of-the-art book will be an invaluable resource for academics and students of environmental law, dispute settlement and public international law. With its practical applications, international judges, litigators and governments will also benefit from the book--
Introduction -- Functions of international litigation -- Access to international courts and tribunals -- Scientific evidence -- Prevention and provisional measures of protection -- Remedies -- Relationships between judicial dispute settlement and non-compliance procedures -- Conclusion.
Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ CIP/ Areesh Education & Trading
Includes bibliographical references and index. (254-295 pages)
Keywords: Environmental law, International -- Trial practice; International courts